THE ECOLOGICAL AND SOCIAL VALUE OF GREEN LOGISTICS - Carp, Elena; Meriacre, Nina; Ovidio, Francesco (CEP USM, 2022)
Green Logistics is a relatively new concept, a part of Green Economy, which considers not just economical aspects but also environmental problems. Unlike classic logistics, that looks only for optimal costs, green logistics is making sure that final decisions won’t have a nega tive effect on the environment or society. It’s making sure that people working in extractions are not exploited, routes are well designed and the environment is not affected. Thanks to Green Logistics concept there were created biofuels, electric trains a nd were discovered so many ways of benefiting from environment without damaging it.
Keywords: fuels; emissions; logistics; environment; transport